The IMPACT OF RETURN ON ASSET, DEBT TO EQUITY RATIO AND INVENTORY TURNOVER ON EFFECTIVE TAX RATE WITH FINANCIAL DISTRESS AS INTERVENING VARIABLE: Case Study on Textile and Garment Sub-Sector Companies Listed on the Indonesia Stock Exchange 2013-2020 - Deni Hamdani; Tamara Prastiyanti (Universitas Indonesia Membangun, 2022)
The purpose of this study was to determine the effect of Return on Assets, Debt to Equity Ratio, and Inventory Turnover on the Effective Tax Rate with Financial Distress as an Intervening Variable. The research uses quantitative methods with descriptive and verification approaches. Testing the data in this study using the classical assumption test, as well as testing the hypothesis using path analysis, correlation coefficient tests, determination coefficient tests, and multiple correlation tests. Data processing using IBM SPSS 26.0 program. Based on the results of this study indicate that (1) Return on Assets has an effect on the Effective Tax Rate. (2) Debt to Equity Ratio has no effect on Effective Tax Rate. (3) Inventory Turnover has no effect on the Effective Tax Rate. (4) Return on Assets has no effect on Financial Distress. (5) Debt to Equity Ratio has an effect on Financial Distress. (6) Inventory Turnover has an effect on Financial Distress. (7) Financial Distress has no effect on the Effective Tax Rate. (8) Return on Assets, Debt to Equity Ratio and Inventory Turnover have a simultaneous effect on the Effective Tax Rate with Financial Distress as an intervening variable.